Factor Predisposition Which Associated with Mother's Behavior in Caring for Stunting Toddlers in Region Work Penengahan Inpatient Health Center, South Lampung 2025 - Ani Kurniawati; Samino; Usatiawaty Cik Ayu SI (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: The South Lampung Health Office has 462 children identified as being at risk of stunting, the Penengahan Inpatient Health Center has 74 children identified as being at risk of stunting, this number has increased from the previous year, which was 66 children. Objective: The purpose of this study was to determine the relationship between predisposing factors and maternal behavior in caring for stunted toddlers. Method: quantitative with a cross-sectional design. The population and sample were all mothers who had toddlers recorded as being at risk of stunting at the Penengahan Inpatient Health Center, South Lampung in 2025, totaling 74 people with a total sampling technique. Data analysis in this study used univariate, bivariate (chi square), and multivariate (multiple logistic regression). Results: The results of this study indicate that there is a relationship between maternal knowledge (p=0.001) with OR: 5.4, maternal attitude (p=0.001) with OR: 5.4, maternal belief (p=0.004) with OR: 4.3, maternal value (p=0.001) with OR: 5.1, maternal perception (p=0.002) with OR: 7.9 with maternal behavior in caring for stunted toddlers in the working area of ​​the Penengahan Inpatient Health Center. The most dominant factor is the perception variable. Conclusion: The study concluded that knowledge, attitude, belief, and perceived value are factors that influence maternal behavior in caring for stunted toddlers. It is recommended that health workers focus interventions on increasing positive perceptions through education, counseling, and ongoing support.